Characteristics of the commercialization of the Cavendish banana crop in the canton of Las Naves (Revista Científica Interdisciplinaria Investigación y Saberes, 2022)
Agricultural production is a necessary activity for the survival of mankind, bananas are one of the products consumed worldwide, and Ecuador is an important producer and marketer of this fruit. Within the exportable supply of the country, bananas represent an important item. This research analyzes the commercialization processes of the Cavendish banana variety in the canton of Las Naves, for which five banana producers of this canton were investigated. The methodology used was descriptive and analytical, applying interviews and surveys to these producers, as well as reviewing secondary information to know the global and specific context of the problem of study. The most important results obtained were: that the producers-traders, who have important volumes, have the possibility of committing their product to the large transnational companies such as Chiquita International Limited, Del Monte, etc., the large producers have integrated the entire marketing process, since they are also wholesalers, so they have warehouses that allow them to sell large volumes produced or fruit from other companies that have been subject to a process of intermediation, in the case of small producers, In the case of small producers, their small volumes do not allow them to sell directly to the central supply center, not even via commission agents, so their sales are made through the local collector, who in turn will sell to the commission agent of the central supply center, who in turn will sell to the wholesaler.